STRATEGY FOR PREPARING CBDC IMPLEMENTATION IN NORTH SUMATRA - Munim, Akhmad; Amelia, Reni (Jurnal BPPK: Badan Pendidikan dan Pelatihan Keuangan, 2024)
This study aims to determine the characteristics and identify the factors that influence the people of North Sumatra who are adaptive to the implementation of CBDC. It is approached by people who access e-banking. We find that characteristics of people who are adaptive to the implementation of CBDC are college graduate; finished high school/equivalent and living in urban areas; and finished high school/equivalent, living in rural areas, and working in processing industries, finance, insurance activities, government administration, defense, compulsory social security, education, human health activities, and social activities. These findings suggest that the CBDC implementation should take into account individual characteristics.